Antenna & Applied Electromagnetic Application - Mohamad Kamal A. Rahim, editor; Ahmad Marwan Mohamad Dahlan, contributor; Bialkowski, Marek E., contributor; Mohamad Kamal A. Rahim, contributor; Mohd. Haizal Jamaluddin, contributor; Mohsen Khalily, 1983-, contributor; Muhammad Ramlee Kamarudin, contributor; Norhudah Seman, contributor; Muhammad Ikram Abdul Razak, contributor; Gillard, Raphael, contributor; Sauleau, Ronan, contributor (Johor Bahru, Johor : Penerbit UTM Press, 2015)
Includes bibliographical references and index